Germany : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Germany. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the economic performance of Germany. The economy of Germany is projected to slowly rebalance, with domestic demand supported by tight labor market, accommodative monetary conditions, and, in 2016, a fiscal expansion. Declining medium-term growth prospects, however, continue to hold back domestic investment and push up savings, preventing faster rebalancing. Progress has been slow on addressing needs in public infrastructure and stimulating competition in services sector, while mounting aging costs and a successful labor market integration of women and refugees require further policy action. Full use of the room available under fiscal rules to finance additional public investment and growth-friendly structural reforms would be appropriate.